Gulliver's travels: Voyage to Lilliput - Jenkins, Martin 1959-; Swift, Jonathan 1667-1745 (Walker Books and Subsidiaries, 2015)
An adaptation of Gulliver's travels containing his extraordinary voyages. Gulliver travels to Lilliput, land of the small; and Brobdingnag, land of giants; to Laputa, where inhabitants need to be hit on the head with sticks to remind them to talk; Glubbdubdrib, island of ghosts and magicians; and the Kingdom of the Houyhnhnm, where horses rule over humans. Suggested level: intermediate, secondary